Harmful impact of morphine use in acute heart failure - Naito, Kotaro; Kohno, Takashi; Fukuda, Keiichi (Journal of Thoracic Disease, 2017)
Acute heart failure, frequently observed in the emergency department, could be a life-threatening condition. Most intravenous therapies introduced for the treatment of acute heart failure continue to be used despite very limited studies (loop diuretics, nitrates) or studies showing their possible harmful effects (inotrope) (1). Likewise in the case of opiates—they continue to be used for some patients with acute heart failure, especially in those presenting with acute pulmonary edema. The use of opiates in the treatment of heart failure dates back to the 1960s, and opiates were considered one of the most important agents for treatment of heart failure in the 1970s (2,3).